Melatonin Reduces Oxidative Stress Damage Induced by Hydrogen Peroxide in Saccharomyces cerevisiae - Vázquez, Jennifer; González, Beatriz; Sempere, Verónica; Mas, Albert; Torija, María Jesús; Beltran, Gemma (Frontiers in Microbiology, 2017)
Melatonin (N-acetyl-5-methoxytryptamine), which is synthesized from tryptophan, is formed during alcoholic fermentation, though its role in yeast is unknown. This study employed Saccharomyces cerevisiae as an eukaryote model to evaluate the possible effects of melatonin supplementation on endogenous cellular defense systems by measuring its effects on various cellular targets. Cell viability, intracellular reduced and oxidized glutathione levels (GSH and GSSG, respectively), reactive oxygen species (ROS) production, and expression of genes related to antioxidant defense in yeast, such as the glutathione system, catalase, superoxide dismutase, glutaredoxin and thioredoxin, were assessed. Melatonin alone decreased GSH, increased GSSG, and activated antioxidant defense system genes, which reached maximum levels in the stationary phase. These results indicate that melatonin supplementation enables cells to resist better the stress generated in the stationary phase. However, when cells were subjected to oxidative stress induced by H2O2, melatonin was able to partially mitigate cell damage by decreasing ROS accumulation and GSH and increasing GSSG; this was followed by enhanced cell viability after stress exposure, mostly when occurring in the early stationary phase. Additionally, under such conditions, most genes related to endogenous antioxidant defense continued to be up-regulated with melatonin supplementation. The findings demonstrate that melatonin can act as antioxidant in S. cerevisiae.